2019
DOI: 10.1136/bmjresp-2019-000429
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcome of central airway obstruction in patients with lung cancer

Abstract: IntroductionCentral airway obstruction (CAO) is a life-threatening complication of lung cancer. The prevalence of CAO in lung cancer patients is unknown. We audited CAO burden to inform our local cancer service.MethodsThis is a cohort review of all new lung cancer diagnoses between 1 November 2014 and 30 November 2015. CAO was defined by CT appearance. CT scans and routine patient records were followed up to 30 November 2018 to determine the prevalence of CAO at diagnosis; the characteristics of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 19 publications
3
41
2
Order By: Relevance
“…Central airway obstruction (CAO) is defined as any disease process affecting the trachea, right and left main bronchus, or bronchus intermedius on imaging or by direct visualization at bronchoscopy. 1 Malignant airway obstruction (MAO) may develop due to a primary intraluminal malignancy, extension of an adjacent tumour with airway invasion, metastatic endoluminal disease, or extrinsic compression from a contiguous malignant process. 2 It is estimated that 20% to 30% of patients with lung cancer have MAO, and 40% of deaths are attributed to progressive locoregional disease.…”
Section: Introductionmentioning
confidence: 99%
“…Central airway obstruction (CAO) is defined as any disease process affecting the trachea, right and left main bronchus, or bronchus intermedius on imaging or by direct visualization at bronchoscopy. 1 Malignant airway obstruction (MAO) may develop due to a primary intraluminal malignancy, extension of an adjacent tumour with airway invasion, metastatic endoluminal disease, or extrinsic compression from a contiguous malignant process. 2 It is estimated that 20% to 30% of patients with lung cancer have MAO, and 40% of deaths are attributed to progressive locoregional disease.…”
Section: Introductionmentioning
confidence: 99%
“…We believe the study adds to the body of literature that thermal ablative interventions relieve airway obstruction and symptoms, thus allowing initiation or continuation of systemic anti-cancer therapy. This is relevant as the prevalence of CAO in lung cancer patients is 13% (13). Many patients have diagnostic delays and often present when are very symptomatic and require hospitalization (2).…”
Section: Discussionmentioning
confidence: 99%
“…A recent single center cohort analysis of 342 newly diagnosed lung cancer patients identified CAO in 45 (13%) patients at the time of diagnosis with an additional 15 patients (5%) developing CAO over a median follow up of approximately one year (4). Of the 45 CAO patients, 23 received a diagnosis during or after a hospital admission for cough or breathlessness (4). A careful review of these 45 CAO patients also found that 14 (31%) did not have CAO reported on index CT imaging (4).…”
Section: Incidence and Prevalencementioning
confidence: 99%